2013
DOI: 10.1111/j.1365-2125.2012.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential drug interactions by characterization of human drug metabolism pathways using non‐invasive bile sampling

Abstract: AIMCharacterization of the biliary disposition of GSK1325756, using a non-invasive bile sampling technique and spectrometric analyses, to inform the major routes of metabolic elimination and to enable an assessment of victim drug interaction risk. METHODSixteen healthy, elderly subjects underwent non-invasive bile capture using a peroral string device (Entero-Test ® ) prior to and following a single oral dose of GSK1325756 (100 mg). The device was swallowed by each subject and once the weighted string was judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
(29 reference statements)
3
16
0
Order By: Relevance
“…Indeed, Entero-Test-collected bile sample analysis confirmed that the glucuronide of GSK1322322 (M9) was the major biliary radiocomponent in humans. Although the Entero-Test, a noninvasive and easy-to-use device, has been used in human bile collections before (Vonk et al, 1986;Muraca et al, 1989;Bloomer et al, 2012), this is the first study, to our knowledge, that it has been successfully incorporated into a conventional human radiolabel study. Biliary metabolites have often been crucial in evaluating drug disposition, especially if the metabolites were unstable after biliary secretion into the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Entero-Test-collected bile sample analysis confirmed that the glucuronide of GSK1322322 (M9) was the major biliary radiocomponent in humans. Although the Entero-Test, a noninvasive and easy-to-use device, has been used in human bile collections before (Vonk et al, 1986;Muraca et al, 1989;Bloomer et al, 2012), this is the first study, to our knowledge, that it has been successfully incorporated into a conventional human radiolabel study. Biliary metabolites have often been crucial in evaluating drug disposition, especially if the metabolites were unstable after biliary secretion into the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GSK pioneered its use in metabolism studies. The device has proven useful in sampling bile from both dogs and human subjects in nonradiolabeled metabolism studies (Guiney et al, 2011;Bloomer et al, 2012), but it has never been tested in a conventional human radiolabel study where its application could be fully evaluated.…”
Section: Gsk1322322 (N-((r)-2-(cyclopentylmethyl)-3-(2-(5-fluoro-6-((mentioning
confidence: 99%
“…It is also possible to get qualitative information into metabolic pathways of orally administered drugs in bile with the use of recent techniques such as Entero-Test (Guiney et al, 2011;Bloomer et al, 2013), although this has not yet been widely adopted. Identification of human-specific metabolic pathways along with any saturable pathways (as indicated by nonlinear PK) guides further refinement of victim DDI potential at FIH stage.…”
Section: New Molecular Entities As Victims Of Metabolic Drug-drug Intmentioning
confidence: 99%
“…Recent advances in clinical devices as Entero-Test (Guiney et al, 2011;Bloomer et al, 2013) have enabled direct assessment of drugs and metabolites excreted into the bile of humans. This method can be applied in early clinical development to provide qualitative information on the risk of interactions for drugs that are metabolized and eliminated in bile.…”
Section: Learning From First-in-human Studiesmentioning
confidence: 99%
“…Application of the Entero-Test has been reported by Bloomer et al (2013), who used this approach to study the metabolism of GSK1325756 (N-(4-chloro-2-hydroxy-3-(3-piperidinylsulfonyl)phenyl)-N9-(3-fluoro-2-methylphenyl)urea), a drug undergoing development for chronic obstructive pulmonary disease. Preliminary in vitro and preclinical studies suggested that the drug underwent direct conjugation, with this conjugate eliminated in bile, as well as additional drug clearance by oxidative metabolism.…”
Section: Approaches To Understanding Metabolite Transportmentioning
confidence: 99%